Fim de uma era ou e agora, Maria? Desafios para a atuaç\~ao federal na educaç\~ao básica - Sergei Soares; Letícia Bartholo; Elaine Cristina Licio; Alvana Bof; Felipe dos Santos Martins; Claudio Hamilton Matos Dos Santos (Instituto de Pesquisa Econômica Aplicada (IPEA), 2021)
– In this text, a newly appointed national secretary of education takes the reader on journey through time across the main dimensions of educational policy, observing its evolution over the last thirty years. Federative relations, financing, evaluation system, curricular parameters, and, of course, teachers training and earnings are all looked at and their evolution summarized. The results of this investment on student outcomes in terms of access, flow, and learning are analyzed. Finally, Maria shares her thoughts on possible trajectories to reach a future in which the quality levels of Brazilian education will leave a future time traveler with a sense of accomplishment. Given the Federative nature of Brazil, Maria understands that it is not up to the Federal Government to directly improve the results of a decentralized policy, but it can - and should - improve the processes that lead to this: coordination, financing and evaluation. In spite of the improvement of the last thirty years, teacher training and earnings and a better curriculum are still needed to improve educational outcomes.
Keywords: I2; H52; 330; basic education; educational policy evaluation; educational policy financing; federative coordination